FAKTOR- FAKTOR YANG MEMPENGARUHI MINAT PERILAKU WAJIB PAJAK UNTUK MENGGUNAKAN E FILLING (Survei PadaWajib Pajak Orang pribadi Di Kabupaten Pati) - Ermawati, Nanik; Kuncoro, Amin (Proceeding SENDI_U, 2016)
SPT reporting system began to follow the development of information technology (online and in real time), is Efilling.The use of E- Filling provide convenience of taxpayers reporting tax return. This study aims to determinefactors that affect the interests of individual taxpayers to use E Filling. Research was conducted on an individualtaxpayer (entrepreneur) in Pati regency. The method used is the method of regression analysis. The data used in thisstudy are primary data, using a questionnaire. The results of this study indicate that the Voluntary use(voluntariness), using the experience (experience), Perceived usefulness (perceived usefulness), attitude towards theuse of (attitude toward using), complexity of use (complexity, affect the interest of taxpayers to use e-filing.Keywords: E-filing, taxpayer interests, individual